2014
DOI: 10.7124/bc.0008b4
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of C60 fullerene-doxorubicin complex towards tumor and normal cells in vitro

Abstract: Creation of new nanostructures possessing high antitumor activity is an important problem of modern biotechnology. Aim. To evaluate cytotoxicity of created complex of pristine C 60 fullerene with the anthracycline antibiotic doxorubicin (Dox), as well as of free C 60 fullerene and Dox, towards different cell types-tumor, normal immunocompetent and hepatocytes. Methods. Measurement of size distribution for particles in C 60 + Dox mixture was performed by a dynamic light scattering (DLS) technique. Toxic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…On the contrary, the studied C 60 fullerene stimulated the growth of HeLa cells (up to 10 %) at their low concentrations (6–12 µg/mL) after 3 h of incubation and the growth of human mesenchymal stem cells cells (up to 30 %) after 1 hour of incubation, Figures , . The similar effect was observed where the application of C 60 FAS induced stimulation of activity of lymphocytes was up to 15 % .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…On the contrary, the studied C 60 fullerene stimulated the growth of HeLa cells (up to 10 %) at their low concentrations (6–12 µg/mL) after 3 h of incubation and the growth of human mesenchymal stem cells cells (up to 30 %) after 1 hour of incubation, Figures , . The similar effect was observed where the application of C 60 FAS induced stimulation of activity of lymphocytes was up to 15 % .…”
Section: Resultssupporting
confidence: 78%
“…We could observe the significant decrease (up to 10%) in the number of viable HeLa cells and human mesenchymal stem cells cells compared with control (untreated cells) at the maximum concentration of C 60 fullerene 24 μg/mL after 24 h (for Hela cells) and 3 h (for human mesenchymal stem cells cells) of incubation, Figure 4A, B. Indeed, according to the data at such concentrations C 60 FAS does not manifest in vitro toxic effect on normal (thymocytes, macrophages and hepatocytes) and tumor (Erlich ascitic carcinoma and leukemia L1210) cells [9][10]26]. At the same time, C 60 FAS exhibits cytotoxic effect against Lewis lung carcinoma cells [27].…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…The antitumor action of the C 60 +Dox nanocomplex was reported to be stronger than the sole action of Dox or С 60 fullerene in vivo [ 23 24 ]. Moreover, recently it was found that C 60 fullerene in C 60 +Dox nanocomplex prevents cyto- and genotoxic effects of Dox on lymphocytes in vitro [ 37 – 38 ]. Based on these results it was suggested that the mechanism of complexation could induce biological synergy for other drugs administered together with C 60 fullerene as well [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor-inhibitory activity of nanoparticles containing C 60 fullerene has been studied in models of murine hepatocarcinoma [ 12 ] and rat colorectal cancer and mammary carcinoma [ 3 , 13 , 14 ]. Finally, recent results indicate that C 60 fullerene complexation with Dox may be a key process leading to alteration of the antitumor effect of Dox in vitro [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%